One-step Synthesis of Ordered Pd@TiO2 Nanofibers Array Film as Outstanding NH3 Gas Sensor at Room Temperature. Issue 1 (December 2017) - Wu, Hongyuan; Huang, Haitao; Zhou, Jiao; Hong, Dahai; Ikram, Muhammad; Rehman, Afrasiab; Li, Li; Shi, Keying
Abstract The one dimensional (1D) ordered porous Pd@TiO2 nanofibers (NFs) array film have been fabricated via a facile one-step synthesis of the electrospinning approach. The Pd@TiO2 NFs (PTND3) contained Pd (2.0 wt %) and C, N element (16.2 wt %) display high dispersion of Pd nanoparticles (NPs) on TiO2 NFs. Adding Pd meshed with C, N element to TiO2 based NFs might contribute to generation of Lewis acid sites and Brønsted acid sites, which have been recently shown to enhance NH3 adsorption-desorption ability; Pd NPs could increase the quantity of adsorbed O2 on the surface of TiO2 based NFs, and accelerated the O2 molecule-ion conversion rate, enhanced the ability of electron transmission. The response time of PTND3 sensor towards 100 ppm NH3 is only 3 s at room temperature (RT). Meantime, the response and response time of the PTND3 to the NH3 is 1 and 14s even at the concentration of 100 ppb. Therefore, the ordered Pd@TiO2 NFs array NH3 sensor display great potential for practical applications.